Analisis Sentimen Komentar Youtube Terhadap Tayangan #Terbaru! Temuan dan Masalah Ahlak Di Ponpes Al-zaytun Menggunakan Metode Naïve Bayes - Mochammad Febrialdi Ansyah; Abd. Ghofur; Lukman Fakih Lidimillah (G-Tech: Jurnal Teknologi Terapan, 2024)
The way to find out feedback from content on social media for look at the comments expressed by the public. This can be studied on branch of computer technology, namely text mining. With text mining, we can extract information from comment data. Sentiment analysis is solution for grouping public responses in the form of comments into positive, neutral and negative comments. On videos about the Al-Zaitun boarding school in News chanel. In this broadcast, information can be obtained from unstructured data, so method is needed to group comment data In this sentiment analysis we use classification using the naïve beyes method. Naïve byes is a simple method but has a good level of accuracy in classification process. This test obtained values ​​of accuracy 64%, recall 93%, precision 75%. This means that it can be concluded that the Naïve Bayes method is suitable for use in sentiment analysis on YouTube comments.